Training and education of specialists in the field of labour law - Kucher, O.; Кучер, О.; Mohilevskyi, L. V.; Могілевський, Л. В. (Journal of Infrastructure, Policy and Development. – 2024. – Vol. 8, Issue 6. – Article 5966, 2024)
У контексті законодавчого середовища, що постійно змінюється, та необхідності підвищення кваліфікації фахівців, дослідження зосереджено на виявленні ефективних методів та інструментів, які сприяють ефективному навчанню та професійному розвитку у сфері трудового права.

Objective/Aim: In the context of a constantly changing legislative environment and the necessity for professionals to develop their skills, the research focuses on identifying effective methods and tools that facilitate efficient learning and professional development in the field of labour law. This study aimed to propose a pedagogical technology for the preparation and training of specialists in the field of labour law and to assess the effectiveness of the training based on the specified technology. Method: The study involved 124 participants, with 63 in the experimental group and 61 in the control group. Statistical analysis was performed using Microsoft Excel. The student’s t-test indicated significant improvements in the experimental group’s training effectiveness, confirming the proposed pedagogical technology’s efficacy. Results: Consequently, implementing training and education technology for specialists in the labour law field was proposed to enhance the indicators. The criteria for the preparation of specialists in the field of labour law were delineated, including knowledge of labour legislation, consulting and support skills, analytical skills, communication skills, and continuous learning. According to the criteria above, levels of preparation for specialists in the field of labour law were established, namely high, medium, and essential. The proposed training and education technology for specialists in the field of labour encompasses the following tools: The utilisation of online platforms and educational resources, virtual classes and simulations, the incorporation of multimedia materials, the integration of adaptive learning technologies, the implementation of project- and problem-oriented teaching methodologies, the incorporation of interactive methodologies, the incorporation of cloud technologies and mobile applications, and the provision of assessment and feedback. Conclusion: The proposed pedagogical technology effectively enhances the training and education of labour law specialists. The experimental group’s significant improvement in learning outcomes confirms the technology’s efficacy. Implication: The findings of this research hold significant social implications. Improved training and education of labour law specialists leads to a more competent and effective legal workforce. This, in turn, ensures better protection of workers’ rights and fairer employer-employee relations, contributing to overall social stability.

В контексте постоянно меняющейся законодательной среды и необходимости повышения квалификации специалистов исследование сосредоточено на выявлении эффективных методов и инструментов, способствующих эффективному обучению и профессиональному развитию в сфере трудового права.
Підготовка та навчання фахівців у сфері трудового права
Keywords: Україна; publikatsii u Scopus; labour law; staff training; professional development; practical skills; specialised training programmes; new trends in labour law; current issues and challenges in labour law; трудове право; навчання персоналу; підвищення кваліфікації; практичні навички; спеціалізовані навчальні програми; нові тенденції в трудовому праві; актуальні проблеми та виклики трудового права